Chemical characterization, antioxidant, enzyme inhibitory and cytotoxic properties of two geophytes: Crocus pallasii and Cyclamen cilicium. (July 2020) - Zengin, Gokhan; Mahomoodally, Mohamad Fawzi; Sinan, Kouadio Ibrahime; Picot-Allain, Marie Carene Nancy; Yildiztugay, Evren; Cziáky, Zoltán; Jekő, József; Saleem, Hammad; Ahemad, Nafees
Graphical abstract: Highlights: Different parts of Crocus pallasii and Cyclamen cilicium were tested. Chemical components were identified for each extracts. Antioxidant, enzyme and cell assays were employed. The root extract of Cyclamen cilicium exhibited the best antioxidant abilities. Observed findings could be valuable for designing industrial bioactive products. Abstract: The Crocus and Cyclamen genus have been reported to possess diverse biological properties. In the present investigation, two geophytes from these genus, namely Crocus pallasi and Cyclamen cilicium have been studied. The in vitro antioxidant, enzyme inhibitory, and cytotoxic effects of the methanol extracts of Crocus pallasii and Cyclamen cilicium aerial and underground parts were investigated. Antioxidant abilities of the extracts were investigated via different antioxidant assays (metal chelating, radical quenching (ABTS and DPPH), reducing power (CUPRAC and FRAP) and phosphomolybdenum). Cholinesterases, amylase, tyrosinase, and glucosidase were used as target enzymes for detecting enzyme inhibitory abilities of the samples. Regarding the cytotoxic abilities, breast cancer cell lines (MDA-MB 231 and MCF-7) and prostate cancer cell lines (DU-145) were used. The flowers extracts of Crocus pallasii and C. cilicium possessed the highest flavonoid content. The highest phenolic content was recorded from C. cilicium root extract (47.62 mg gallic acid equivalent/g extract). Cyclamen cilicium root extract showed significantly ( p < 0.05) high radical scavenging (94.28 and 139.60 mg trolox equivalent [TE]/g extract, against DPPH and ABTS radicals, respectively) and reducing potential (173.30 and 109.53 mg TE/g extract, against CUPRAC and FRAP, respectively). The best acetylcholinesterase, glucosidase and tyrosinase inhibition was observed in C. cilicium root (4.46 mg GALAE/g; 15.75 mmol ACAE/g; 136.99 mg KAE/g, respectively). Methanolic extracts of C. pallasii and C. cilicium showed toxicity against breast cancer cell lines. In light of the above findings, C. cilicium might be considered as an interesting candidate in the development of anti-cancer agent coupled with antioxidant properties.